(untitled) (Bangladesh Journal of Agricultural Research, 2016)
An experiment was conducted at the research field of Department of Agronomy, Bangladesh Agricultural University, Mymensingh during June to December 2012 to investigate the effect of age of tiller seedlings, number of tiller seedlings hill-1 and application of urea super granules (USG) on the yield and yield contributing characters of transplant Aman rice (cv. BRRI dhan52). The experiment consisted of two ages of tiller seedlings viz. 25 and 35-days old, three levels of tiller seedlings hill-1 viz. 1, 3 and 5 seedlings hill-1 and three levels of USG viz. 0, 1.8 (55 kg N ha-1) and 2.7g USG (80 kg N ha-1) four hill-1 in every alternate row. The experiment was laid out in a Randomized Complete Block Design (Factorial) with three replications. The highest plant height, number of effective tillers hill-1, number of total tillers hill-1, number of total spikelets panicle-1, number of grains panicle-1, grain yield and harvest index were found in 1.8 g USG applied @ one granule 4-hill-1. The highest number of sterile spikelets panicle-1 was found in control treatment and the lowest in 1.8 g USG. The highest number of effective tillers hill-1, number of total spikelets panicle-1 and grain yield ha-1 was found when 5 tiller seedlings were transplanted hill-1 combined with 1.8 g USG. Application of urea super granules 1.8 g (55 kg N ha-1) at 10 days after transplanting @ one granule 4-hill-1 in every alternate row with 25 day old tiller seedlings using 5 tiller seedlings hill-1 was found beneficial for grain yield of transplant Aman rice. Tiller separation could be an alternative source of seedling during seedling scarcity. Bangladesh J. Agril. Res. 40(4): 581-590, December 2015